Improving The Knowledge of Chinese Culture Through Paper Cutting Art Training - Lily Thamrin; Suhardi Suhardi; Tjen Veronika; Lusi Lusi (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2020)
The art of cutting paper or China cutting paper is one of the Intangible Cultural Heritage (WBTB) that has been recognized by UNESCO. Culture is the legacy of our ancestors passed down from generation to generation. This paper cutting training was intended to increase students' knowledge of Chinese culture. The method used was to provide training and socialization about Chinese cultural knowledge. The training participants were 80 students from various universities in Pontianak. The response of the participants in this training was excellent. The participants were very enthusiastic about participating in all training activities. Moreover, after they mastered the paper cutting technique and produced their work, they were delighted. They hope that this training activity can be carried out even longer and more varied time in the future.